The 2nd International Congress on 3D Materials Science Congress Proceedings - Bernard, Dominique; Buffière, Jean-Yves; Pollock, Tresa; Friis Poulsen, Henning; Rollett, Anthony; Uchic, Michael (The Minerals, Metals & Materials Series,, 2016)
This is a collection of papers presented at the 2nd International Congress on 3D Materials Science, an event organized by The Minerals, Metals & Materials Society (TMS). The conference provides the premier forum for presentations of current interest and significance to the three-dimensional characterization, visualization, quantitative analysis, modeling, and investigation of structure-property relationships of materials. The papers presented in the collection are divided into six sections: (1) Acquisition and Handling of 3D Data; (2) Microstructure/Property Relationship in 3D: Characterization and Simulation; (3) Microstructure/Property Relationship in 3D: Deformation and Damage; (4) New Experimental Techniques; (5) Analysis at the Nanoscale; and (6) Dynamic Processes.